2000
DOI: 10.1038/sj.bmt.1702460
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of unrelated bone marrow donor searches in 174 children resulting in 45 patients transplanted in the HLA-matched and -mismatched situation

Abstract: Summary:The aim of the study was to evaluate the outcome of unrelated bone marrow donor (UBMD) searches initiated for 174 children between 1986 and 1997. Seven patients were registered twice so that a total of 181 UBMD searches took place. At the time of registration, patients suffered from hematological malignancies (n = 121), non-malignant hemopathies (n = 26) and inborn errors (n = 34). Forty-five of the patients (26%) were given transplants from unrelated donors of whom 26 (58%) were HLA-mismatched transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…26,27 This improvement is mainly due to refinements in HLA typing, GvHD prophylaxis, timing of SCT, and supportive care. It has recently been reported that matching HLA class I and class II alleles of the donor and recipient can significantly improve outcome after UD BMT, 28 but, in keeping with Souillet et al, 29 the aim of the search strategy should be to carry out a transplant within 3 months from search activation. In the absence of a fully compatible donor, a one-antigen mismatched unrelated volunteer donor can be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 This improvement is mainly due to refinements in HLA typing, GvHD prophylaxis, timing of SCT, and supportive care. It has recently been reported that matching HLA class I and class II alleles of the donor and recipient can significantly improve outcome after UD BMT, 28 but, in keeping with Souillet et al, 29 the aim of the search strategy should be to carry out a transplant within 3 months from search activation. In the absence of a fully compatible donor, a one-antigen mismatched unrelated volunteer donor can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a fully compatible donor, a one-antigen mismatched unrelated volunteer donor can be considered. 29 In this study, the outcome of the cohort of patients undergoing other types of SCT should be considered with caution, due to the heterogeneity of transplants and to the small number of analyzed patients. About half of these alternative transplants were performed during a more advanced phase, at a median time of 10.6 months after search activation.…”
Section: Discussionmentioning
confidence: 99%
“…The disease-free survival rate appears similar in young patients for which HLA incompatibility is limited to one HLA class I locus. 32 Therefore, for pediatric patients with advanced disease, finding one HLA class I-mismatched donor within a short time would be preferable to searching for a perfectly matched donor for a longer time. In this regard, it seems appropriate to search in a donor pool with one HLA broad mismatch when analysis of patient HLA genotype reveals that matching at the genomic level will be unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…The stem cell source was: unmanipulated bone marrow for related donor-SCT (n ¼ 39); peripheral blood stem cells (n ¼ 2), cord blood stem cells (n ¼ 2) and unmanipulated bone marrow (n ¼ 51) for unrelated donor-SCT. Methods of HLA typing for patients and donors are described in detail by Souillet et al 7 Patient and donor characteristics are described in Table 1.…”
Section: Patients and Donorsmentioning
confidence: 99%